Metamorphic texture in mafic granulites collected from talus in the Brattnipene, Sør Rondane Mountains, East Antarctica - Baba, Sotaro; Uesato, Moeko; Hokada, Tomokazu; Adachi, Tatsuro; Osanai, Yasuhito; Nakano, Nobuhiko; Toyoshima, Tsuyoshi; 馬場, 壮太郎; 上里, 萌子; 外田, 智千; 足立, 達朗; 小山内, 康人; et al. (琉球大学教育学部, 2018)
Retrograde metamorphic P－T paths of garnet—pyroxene—bearing mafic gneisses from the Brattnipene nunataks in Sør Rondane Mountains, East Antarctica, were examined. The majority of samples preserve irregular—shaped garnet coexisting with clinopyroxene, quartz and plagioclase that developed around magnetite, ilmenite and orthopyroxene. The garnet contains fine—grained worm—like quartz inclusions. The occurrences are common in other mafic gneisses in northern Brattnipene and are interpreted as isobaric cooling textures. In another sample, garnet porphyroblasts have been replaced by symplectites of fine orthopyroxene and plagioclase. The mineral textures indicate near isothermal decompression. Retrograde P－T conditions estimated from rock containing orthopyroxene—plagioclase symplectite are within the range of 6.5 ~ 7.2 kbar, 700 ~ 780℃. Previous reports have revealed that metamorphism around Brattnipene is characterized by counterclockwise P－T path involving near—isobaric cooling. Our new finding suggests that metamorphic rocks formed by isothermal decompression should be present at higher altitude in the Brattnipene or relevant nunataks. 紀要論文 http://purl.org/coar/resource_type/c_6501